Desıgn Of Matchıng Impedance And Amplıfıer Cırcuıt For Partıal Dıscharge Measurement - Mahesh Kumar K M1, Dr. B Ramachandra2 (International Journal of Advanced Science and Technology, 2020)
Partial discharges are consequence of local electrical stress concentration in the insulation. Thedetection of partial discharge at the early stage is useful to predict the condition of the powerequipments. The discharge appears as pulse of duration of much less than one micro seconds. PDmeasurements are important diagnostic tools to monitor the insulation condition. Measuring impedanceare used to decouple the PD Current pulses appearing in series with a coupling capacitor to convert itinto voltage pulses for analysis with PD measuring circuit.The paper deals with design of LCR circuit as matching impedance and as per IEC standard design ofsuitable amplifier circuit to amplify signal. The designed circuit is tested observe PD signal appearingacross pigtail specimen inserted in liquid insulator.